Association of circulating tumor cells and IMP3 expression with metastasis of osteosarcoma - Dai, Shuangwu; Shao, Xinxin; Wei, Qingzhu; Du, Shaohua; Hou, Changhe; Li, Haomiao; Jin, Dadi (Frontiers in Oncology, 2023)
Background: Circulating tumor cells (CTCs) have been identified as a prognostic biomarker of epithelial tumors, but its clinical significance in tumors of mesenchymal origin is still unclear. In this study, we analyzed the relationship between CTCs and clinicopathological features, and discussed whether CTCs could be used as biomarkers for metastasis in osteosarcoma. Methods: We enrolled 50 osteosarcoma patients with Enneking Stage IIB-III and detected CTCs in 5 ml peripheral blood samples using the Canpatrol® CTC detection platform, which isolated CTCs according to the size. Subsequently, multiplex RNA in situ hybridisation (RNA-ISH) based on various molecular markers was performed to identify and classify CTCs. The relationships between clinical pathological features and CTCs counts, subtypes (epithelial type, E type; hybrid epithelial/mesenchymal type, H type; mesenchymal type, M type), and IMP3 expression in CTCs were analyzed. Results: CTCs was detected in 86% (43/50) of the patients. The CTCs counts, especially the total CTCs and H type CTCs, signifcantly differed between Enneking Stage IIB and Stage III patients. No signifcant diferences were observed between the CTCs count or type and other clinicopathological features. There are significant differences in the expression of IMP3 in different types of CTCs, and the IMP3 positive rates in E/H/M type CTCs are 38.4 %, 65.6 %, and 62.0 % , respectively (P < 0.001). Receiver operating characteristic (ROC) curve analysis showed that IMP3 positive CTCs count had the best performence for diagnostic metastasis, with the largest area under the curve of 0.873 and cutoff value of 4 cells/5ml blood (sensitivity = 87.5%, specificity = 82.4%). Serial CTCs monitoring in one patient suggested that total CTCs and H type CTCs were associated with disease progression. Conclusion: This study demonstrated that the CTCs count, especially the IMP3 positive CTCs and H/M type CTCs, was related to the metastasis of osteosarcoma.